2021
DOI: 10.3389/fspor.2021.682861
|View full text |Cite
|
Sign up to set email alerts
|

Adaptability to Balance Perturbations During Walking as a Potential Marker of Falls History in Older Adults

Abstract: Given that falls most commonly occur during walking due to unexpected balance perturbations like trips and slips, walking-based balance assessment including walking stability and adaptability to such perturbations could be beneficial for fall risk assessment in older adults. This cross-sectional study reanalyzed data from two larger studies conducted with the same walking protocol. Participants completed unperturbed walking trials at speeds of 0.4 m/s up to 1.8 m/s in 0.2 m/s steps. Ten unannounced treadmill b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 27 publications
1
22
0
Order By: Relevance
“…The obvious advantage of the treadmill in comparison to such overground setups is that predicting when a perturbation will be applied is more difficult, as there is no location-based reference point ( 31 ), which ensures that predictive adjustments in in anticipation of perturbations are reduced [though not necessarily completely absent ( 123 , 155 )]. However, walking on a treadmill can provide additional challenges in some populations at increased fall risk, due to lack of familiarity and the requirement to maintain a specific speed [walking speed can be instantaneously adjusted in an overground setup but maintaining it provides an additional challenge during perturbed treadmill walking ( 205 )]. Another inherent limitation in some setups is that the perturbations themselves may not strictly mimic common causes of falls like slips and trips ( 60 ) despite the subsequent recovery mechanics being suggested to be similar ( 53 , 54 ) (see also Figure 2 in section What is task-specificity in the context of PBT?).…”
Section: Implementation In Practicementioning
confidence: 99%
“…The obvious advantage of the treadmill in comparison to such overground setups is that predicting when a perturbation will be applied is more difficult, as there is no location-based reference point ( 31 ), which ensures that predictive adjustments in in anticipation of perturbations are reduced [though not necessarily completely absent ( 123 , 155 )]. However, walking on a treadmill can provide additional challenges in some populations at increased fall risk, due to lack of familiarity and the requirement to maintain a specific speed [walking speed can be instantaneously adjusted in an overground setup but maintaining it provides an additional challenge during perturbed treadmill walking ( 205 )]. Another inherent limitation in some setups is that the perturbations themselves may not strictly mimic common causes of falls like slips and trips ( 60 ) despite the subsequent recovery mechanics being suggested to be similar ( 53 , 54 ) (see also Figure 2 in section What is task-specificity in the context of PBT?).…”
Section: Implementation In Practicementioning
confidence: 99%
“…Two older adult performance studies assessed fall risk prospectively (Ackermans et al, 2021; Hansson et al, 2021), by following subjects for one year to determine whether they fall, after they performed the challenging walking task. Six studies assessed fall risk retrospectively (Brach et al, 2011; Oh-Park et al, 2011; Uemura et al, 2011; Ackermans et al, 2019; Pieruccini-Faria and Montero-Odasso, 2019; Guadagnin et al, 2020; Gerards et al, 2021), by asking subjects at the time of the walking measurement whether they had fallen in the previous months. Three studies evaluated risk based on physical or mental performance at the time of the walking measurement using clinical tests or questionnaires (Zietz et al, 2011; de Carli et al, 2014; Pan et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…The obvious advantage of the treadmill in comparison to such overground setups is that predicting when a perturbation will be applied is more difficult, as there is no location-based reference point (McCrum et al, 2017b), which ensures that predictive adjustments in in anticipation of perturbations are reduced (though not necessarily completely absent (Wang et al, 2019b, Dusane and). However, walking on a treadmill can provide additional challenges in some populations at increased fall risk, due to lack of familiarity and the requirement to maintain a specific speed (walking speed can be instantaneously adjusted in an overground setup but maintaining it provides an additional challenge during perturbed treadmill walking (Gerards et al, 2021b)). Another inherent limitation in some setups is that the perturbations themselves may not strictly mimic common causes of falls like slips and trips (Song et al, 2021) despite the subsequent recovery mechanics being suggested to be similar (Owings et al, 2001 (see also Figure 2 in section 2.2).…”
Section: What Technology Is Required For Pbt?mentioning
confidence: 99%